Suboptimal reliability of FIB‐4 and NAFLD‐fibrosis scores for staging of liver fibrosis in general population - Rawi Hazzan; Nur Abu Ahmad; Abu Shqara Habib; Igbaria Saleh; Neeman Ziv (JGH Open, 2024)
Abstract Background and Aim The burden and incidence of liver cirrhosis are increasing worldwide. Early detection of liver fibrosis would help in early interventions and preventing the progression of fibrosis and cirrhosis. The accepted noninvasive markers for liver fibrosis staging, namely fibrosis‐4 (FIB‐4) and nonalcoholic fatty liver disease fibrosis score (NFS), have shown inconsistent performance for detecting the fibrosis stage. We aimed to evaluate the efficacy of FIB‐4 score and NFS for the detection of liver fibrosis in the general population. Methods From a general population referred from a single, community‐based family‐physician clinic, we included study participants between the ages of 45 and 65 years, with no knowledge of liver disease and no record of alcohol consumption. Liver fibrosis was evaluated by the FIB‐4 score and NFS using shear wave elastography (SWE) or transient elastography (TE) measurements as a reference. Results A total of 76 participants (aged 61.5 ± 0.37 years, 33% females) were included in the study cohort. We observed a nonsignificant correlation between liver stiffness measurement (LSM) and FIB‐4 and NFS (r = 0.1, P = 0.37; r = 0.16, P = 0.15, respectively). Our results showed that only 5.2% with FIB‐4 >3.25 and 9.7% with NFS >0.675 had LSM >12 kPa. The compatibility of fibrosis staging was 55% between FIB‐4 score and LSM and only 18% between NFS and LSM. Conclusion We found that FIB‐4 and NFS are unreliable tools for liver fibrosis estimation in the general population. There is a need for more reliable noninvasive methods for the early detection of liver fibrosis.